Combined Treatment of Photobiomodulation and Arginine on Wound Healing in an Animal Model of Delayed Healing Wound: Photobiomodulation and Arginine on Chronic Wound Healing - Mostafavinia, Atarodsadat; Amini, Abdollah; Ahmadi, Houssein; Rezaei, Fatemehsadat; Ghoreishi, Seyed Kamran; Chien, Sufan; bayat, mohammad (Journal of Lasers in Medical Sciences, 2021)
Introduction: Herein, the individual and combined effects of photobiomodulation (PBM) and arginine (ARG) on the wound healing course of an experimental model of a slow healing wound (ulcer) in rats were assessed. Methods: A total of 108 male rats were divided into 6 groups: control; lower energy density (low)-PBM; arginine ointment (ARG); low-PBM+ARG; high energy density (high)-PBM; and highPBM+ARG. In each rat, one ischemic wound in the center of a bipedicle flap and one non-ischemic wound out of the flap was created. Both wounds were treated in the experimental groups. Microbial growth wound area and wound strength were assessed on days 0, 5, 10, 15, and 20 after the wound. infliction Results: All non-ischemic wounds closed before day 15. High-PBM+ARG and ARG significantly increased wound closure rates compared to the control group (LSD test, P=0.000, and P=0.001, respectively) on day 10. All slow healing wounds were open on day 15 but closed completely before day 20. Low-PBM+ARG and high-PBM significantly increased wound strength (stress high load, SHL) on day 10 compared to the control group (LSD test, P=0.001, and P=0.000, respectively). ARG, high-PBM, and low-PBM+ARG significantly increased wound closure rates on day 15 relative to the control group (LSD test, P=0.000, P=0.000, and P=0.001, respectively). Conclusions: High-PBM and low-PBM+ARG have biostimulatory and antibacterial effects on slow-healing wounds, which were shown by significant increases in wound closure rates, wound strength, and inhibition of Staphylococcus aureus growth. Doi:10.34172/jlms.2021.40.